The Migration Pathway Of Some Selected Australian Palynomorphs From Their Origin To Se Asia - Eko Budi Lelono (Scientific Contributions Oil and Gas, 2012)
This paper proposes the alternative dispersal route of Australian elements of Dacrydium and Casuarina from their origin to Southeast Asia. It was previously thought that these Australian affi nities migrated to Sunda region following the collision of the Australian and the Asian plates at the Oligo-Miocene boundary (Morley, 1998 and 2000). The subsequent study by Lelono (2007) extended the record of these two taxa from the Oligo-Miocene boundary to the base Oligocene. This is unlikely, since at the time of basal Oligocene, when these pollen types fi rst appear, the Australian land mass would have been some 1000 kms south of the East Java area. Therefore, this fact led Lelono (2007) to propose the earlier arrival of the Gondwanan fragment to this area in Early Oligocene. However, recent records of Dacrydium have been reported from the Early Eocene of the Ninety East Ridge (55 Ma) and the Indian subcontinent (50 Ma) (Morley, 2009). This implies to the alternative dispersal route of this pollen. It is possible that Dacrydium dispersed into SE Asia prior to the Early Oligocene via the Ninety East Ridge and the Indian plate, and subsequently its distribution across the Sunda region and Indochina was limited by palaeoclimate, explaining why it is present in some areas of the Sunda region, but not others. Mean while, a model to explain the dispersal of Casuarina remains unresolved, since migration via India is unlikely as there is no pollen record from the Indian subcontinent. Therefore, long distance dispersal may be a possibility for this pollen.